Epicenters of dynamic connectivity in the adaptation of the ventral visual system. Issue 4 (28th December 2016) - Prčkovska, Vesna; Huijbers, Willem; Schultz, Aaron; Ortiz‐Teran, Laura; Peña‐Gomez, Cleofe; Villoslada, Pablo; Johnson, Keith; Sperling, Reisa; Sepulcre, Jorge
Abstract: Objectives and design : Neuronal responses adapt to familiar and repeated sensory stimuli. Enhanced synchrony across wide brain systems has been postulated as a potential mechanism for this adaptation phenomenon. Here, we used recently developed graph theory methods to investigate hidden connectivity features of dynamic synchrony changes during a visual repetition paradigm. Particularly, we focused on strength connectivity changes occurring at local and distant brain neighborhoods. Principal observations : We found that connectivity reorganization in visual modal cortex—such as local suppressed connectivity in primary visual areas and distant suppressed connectivity in fusiform areas—is accompanied by enhanced local and distant connectivity in higher cognitive processing areas in multimodal and association cortex. Moreover, we found a shift of the dynamic functional connections from primary‐visual‐fusiform to primary‐multimodal/association cortex. Conclusions : These findings suggest that repetition‐suppression is made possible by reorganization of functional connectivity that enables communication between low‐ and high‐order areas. Hum Brain Mapp 38:1965–1976, 2017 . ©2017 Wiley Periodicals, Inc.